Mather’s behavior and motivations for children oral health care in the Ammatoa Tribe of Kajang-Bulukumba, South Sulawesi-Indonesia - Yudha Rahina; Rasmidar Samad; Nursyamsi Djamaluddin; Surwandi Waliyanto (DiscoverSys Inc., 2021)
Objectives: This study aimed to discribe mother’s behavior and motivation in caring of children oral health in Bulukumba District, South Sulawesi. Methods: A priliminary study was conducted to 18 preschool’s mothers of children who attend dental health education as health cadres. Data were collected using questionnaires and structured interview. The data were analyzed qualitatively. The motivation data were analyzed by Wilcoxon signed ranks test.Results: Mother's behavior show good results 11.11%, fair 55.56%, and poor 33.33%. All mothers have good motivation. There is significant diferences motivation before and after dental health education (p=0.00).Conclusion: Just a little mothers have good behavior. Dental health care for children has not become a major concern for parents. All of mother have good motivation to change their unbeneficial behavior of oral health care for their children after having education.